2003
DOI: 10.1007/s00268-003-6751-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Correction of Main Stem Reflux in the Superficial Venous System: Does It Improve the Blood Flow of Incompetent Perforating Veins?

Abstract: Fifty-seven limbs (33 patients) with chronic venous ulceration were selected for this study. The criterion for selection was the presence of isolated superficial venous reflux. Long saphenous vein reflux alone was observed in 39 (68.4%) limbs, short saphenous vein reflux alone in 4 (7.0%) limbs, and both long and short saphenous vein reflux in 14 (24.6%) limbs. Surgical correction of the refluxing saphenous system has allowed 46 (80.7%) ulcers to heal. The healing rates for all the ulcerated legs that had long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
5
17
2
4
Order By: Relevance
“…Duplex scanning is the primary non-invasive method of assessing chronic venous insufficiency, which has an overall accuracy of 94%. This finding is in conformity of Masuda et al 12 who showed that duplex scanning had an overall accuracy of 88%.…”
Section: Duplex Scansupporting
confidence: 92%
“…Duplex scanning is the primary non-invasive method of assessing chronic venous insufficiency, which has an overall accuracy of 94%. This finding is in conformity of Masuda et al 12 who showed that duplex scanning had an overall accuracy of 88%.…”
Section: Duplex Scansupporting
confidence: 92%
“…DVI is rarely the primary cause. The correlation between the occurrence of insufficiency of GSV and PVs has been revealed [6,[14][15][16][17]. In many studies and our study, PVI was found to be most frequently associated with insufficiency in deep veins, GSV, SSV, anterior/posterior accessory GSV, and chronic DVT.…”
Section: Discussionmentioning
confidence: 77%
“…However, CDUS at three or six months revealed partial recanalization of two GSVs and one SSV (5%). The median numbers of incompetent PVs and all PVs per limb were 2 (range, 0-7) and 8 (range, 3-16) preoperatively, whereas they were 3 (range, 0-7) and 8 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] postoperatively. EVLA did not change the proportion of incompetent PVs (preoperatively, 154/483 [32%] vs. postoperatively, 167/501 [33%], P = 0.173), but resulted in a significant increase in the total number of all PVs (preoperatively, n=483 vs. postoperatively, n=501; P = 0.036).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, surgical eradication of superficial venous reflux offloads the deep venous compartment sufficiently to reduce dilatation and reverse perforator incompetence (11). However, saphenous surgery alone failed to correct incompetence of PVs in patients with superficial reflux that persists postoperatively, or when there is coexistent deep venous reflux (11,13). Statistical evaluation for correction of PV incompetency did not include multivariate analysis in those studies.…”
Section: Discussionmentioning
confidence: 99%